Diversity competence training for health professionals in Europe: a modified delphi study investigating relevant content for short or online courses - Sørensen, Janne; Michaëlis, Camilla; Olsen, Julie Marie Møller; Krasnik, Allan; Bozorgmehr, Kayvan; Ziegler, Sandra (BMC medical education, 2023)
Diversity is a reality in our societies, requiring health professionals to adapt to the unique needs of all patients, including migrants and ethnic minorities. In order to enable health professionals to meet related challenges and reduce health disparities, long and demanding training courses have been developed. But due to busy schedules of professionals and often scarce resources, a need for shorter training courses exists. This study aims to investigate which topics and methods should be prioritised in designing basic diversity training courses that provide health professionals the opportunity to foster this competence.